(untitled) (Research, Society and Development, 2020)
The impact of the COVID-19 pandemic has influenced the behavior of all individuals, especially those who are in direct contact with infected people. Nursing professionals play an important role in coping with COVID-19. However, nursing needs adequate and safe working conditions, with access to personal protective equipment for their protection. This study aimed to gather urgent and long-term strategies that can be adopted to promote the health of these professionals.